Management of Post-partum Complete Cervico-uterine Prolapse in Crossbred Jersey Cow - Behera, Himanshu; Bhumij, Bijay Kumar; Prasad, Uppumaguluri Venkata Sai Narayan; Behera, Manoj Kumar; Pradhan , Tarinee Ranjan (The Indian Journal of Animal Reproduction, 2023)
Post-partum uterine prolapse is a very common obstetrical problem as it affects the future breeding and production of an animal. It generally leads to delay in return to oestrus and subsequently reduction in conception rate and thus increase in the inter calving period of a female animal. In the present case, in a postpartum crossbred cow, replacement and repositioning of the cervix and uterus was done under caudal epidural anaesthesia with the horizontal mattress suture on vulva. The suture was removed after 14 days on complete recovery of the animal.
Keywords: Cervico uterine prolapse; Epidural anaesthesia; Retention suture; Antibiotics